Plasma Hormones, Lipid Profile and Productive Performance During Early Lactation in Crossbred Cows Supplemented with Prilled Fat - Gnanasekar, Rajesh; Singh, Mahendra; Roy, Ashwani Kumar; H.M., Ajithakumar; Thakur, Sunita (Indian Journal of Animal Nutrition, 2018)
Twelve crossbred Karan Fries cows were divided into 2 groups viz., control (CON) and supplemented group (SG) based on milk yield (16.60 vs. 16.45 kg/d) and days in milk (20.01 vs. 21.0 days). The SG cows were fed prilled fat @ 75 g/d/animal from day 30 to 120 days of lactation. Body weight and body condition score were recorded. Plasma hormones and lipid profile were estimated at fortnightly intervals. Feeding of prilled fat did not influence feed intake, plasma prolactin, insulin, cortisol, T3 and T4 levels. The supplementation of prilled fatincreased plasma triglycerides level (P